2016
DOI: 10.1080/00794236.2016.1169490
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and the spread of capitalism: material resonances

Abstract: Word count (including notes and bibliography):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Ideas of freedom and progress are closely connected to individualization, which lies at the basis of capitalist ideology (Johnson 1996 :203; Leone 1999a :211). The ethos of self-improvement, the possibility to climb up the social ladder if only one tries hard enough, conceals the many inequalities within the system (Horning and Schweickart 2016 :36). The materialized segregation into classes reinforces the social position of those aboard, but it simultaneously reflects the promise of a better life through hard work.…”
Section: Discussionmentioning
confidence: 99%
“…Ideas of freedom and progress are closely connected to individualization, which lies at the basis of capitalist ideology (Johnson 1996 :203; Leone 1999a :211). The ethos of self-improvement, the possibility to climb up the social ladder if only one tries hard enough, conceals the many inequalities within the system (Horning and Schweickart 2016 :36). The materialized segregation into classes reinforces the social position of those aboard, but it simultaneously reflects the promise of a better life through hard work.…”
Section: Discussionmentioning
confidence: 99%
“…Or an unremarkable everyday object of so little value that it escaped attention in the packing up of the household effects? 106 These considerations make no explicit reference to cost of the vessel (V 1 ), but the 'informed imagining' of its value (V 2 ) is based on knowledge of the material's provenance and the owner's life history.…”
Section: Archaeological Approaches To Valuementioning
confidence: 99%
“…In the same 2016 anniversary issue of PMA, Horning and Schweickart observed that, in the first 20 years of the journal's history, the term capitalism never appeared, and was only sporadically invoked in the following 30 years. 2 Karl Marx was not directly referenced until 2008. 3 The essays in this issue not only correct that oversight, but more importantly seek to reposition the role and understanding of political economy, and in many instances overlapping political economies, as a productive vehicle for exploring and understanding the complexities of the early modern and modern worlds.…”
mentioning
confidence: 99%